High hydrostatic pressure (HHP) reinforces solid encapsulation of d-limonene into V-type starch and its application in strawberry storage - Yanan, Sun; Xiangze, Jia; Chin, Ping Tan; Bin, Zhang; Xiong, Fu; Qiang, Huang (Elsevier, 2023)
The formation of inclusion complexes (ICs) between V-type starch and flavors is traditionally conducted in an aqueous system. In this study, limonene was solid encapsulated into V6-starch under ambient pressure (AP) and high hydrostatic pressure (HHP). The maximum loading capacity reached 639.0 mg/g after HHP treatment, and the highest encapsulation efficiency was 79.9 %. X-ray Diffraction (XRD) results showed that the ordered structure of V6-starch was ameliorated with limonene, which avoided the reduction of the space between adjacent helices within V6-starch generated by HHP treatment. Notably, HHP treatment may force molecular permeation of limonene from amorphous regions into inter-crystalline amorphous regions and crystalline regions as the Small-angle X-ray scattering (SAXS) patterns indicated, leading to better controlled-release behavior. Thermogravimetry analysis (TGA) revealed that the solid encapsulation of V-type starch improved the thermal stability of limonene. Further, the release kinetics study showed that a complex prepared with a mass ratio of 2:1 under HHP treatment sustainably released limonene over 96 h and exhibited a preferable antimicrobial effect, which could extend the shelf life of strawberries.